The role of rationality in moderating the relationship between extremist mindsets and schizotypy, autism and emotionality - King, Maisie S. (2020)
What makes an individual vulnerable to extremism is complex, though it is likely idiosyncratic. In this research schizotypy, autism, and emotionality were chosen as traits to explore due to shared deficits in cognitive abilities, socio-emotional functioning, and perceptual processing which makes these also predictors of risk taking and offending. Not all people with these qualities offend or take risks, subsequently rational and experiential thinking was chosen as a moderator between these traits and a militant extremist mindset. Over 990 participants completed scales measuring schizotypy (OLIFE), autism (RAADS-14), emotionality (HEXACO-E), rationality (REI) and militant extremist mindsets (MEM). Traits of schizotypy and autism were significantly related to extremist mindset. Schizotypal unusual experiences, introvertive anhedonia, impulsive nonconformity, and autism’s mentalising deficits were the most significant predictors for extremist mindset. Rational and experiential thinking had a significant moderation effect these relationships, indicating rationality can moderate the relationship between schizotypy, autism and militant extremist mindsets. Emotionality showed no significant relationship with extremist thinking styles. This study shows rational thinking is important in moderating extremist thinking in people with schizotypal or autism-related traits, which are identified as possible vulnerabilities for extremist ideation, and can be developed into preventative interventions to counter the development of extremist mindsets in those identified as vulnerable.